"'Tis Time Must Do": Schopenhauer and Shakespearean Romantic Time. (3rd July 2019) - Day, Jonathan
ABSTRACT: The intersection between the will and early modern texts is an area of increasing scholarly focus. The collision of the central early modern author with one of the key theorists of will sparks new critical fires, and turning from Schopenhauer's focus upon tragedy to Shakespearean romance offers exciting new possibilities. Schopenhauer's theory of aesthetics suggests that art has two roles, palliative and cognitive. The art of genius both soothes the human experience of the world as a tragedy and provides insight into the world beyond the veil of appearances, of things beyond time. This essay posits that Shakespearean romance displays Schopenhauer's belief that existence is, at root, not rational and, moreover, that it brings forth his suggestion that existence is essentially illusion through the bold interplay of time with dreams, the sea and personal identity. It also argues both that romances' persistent engagements with time and the strange manner of their dénouements are fully in keeping with Schopenhauer's view that art's reprieve is temporary, and that the plays foreground their own transient natures as phenomena bounded by time. This article demonstrates how Schopenhauer's philosophy can serve as a productive lens for examining our experience of time in Shakespearean drama.